2011
DOI: 10.1029/2010gc003343
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave anisotropy in the crust, mantle wedge, and subducting Pacific slab under northeast Japan

Abstract: [1] To study the anisotropic structure beneath northeast (NE) Japan, we made 4366 shear wave splitting measurements using high-quality seismograms of many earthquakes occurring in the crust and the subducting Pacific slab. Our results provide important new information on the S wave anisotropy in the upper crust, lower crust, mantle wedge, and subducting Pacific slab. In the upper crust, the anisotropy is mainly caused by the stress-aligned fluid-saturated microcracks. The measured delay times (DTs) increase to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
123
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(135 citation statements)
references
References 63 publications
12
123
0
Order By: Relevance
“…These Vp anisotropy results have been confirmed and improved by later studies using better data sets for a few individual areas in Tohoku Huang et al (2011a). The red and blue triangles denote the active and quaternary arc volcanoes, respectively.…”
Section: Northeast Japansupporting
confidence: 82%
“…These Vp anisotropy results have been confirmed and improved by later studies using better data sets for a few individual areas in Tohoku Huang et al (2011a). The red and blue triangles denote the active and quaternary arc volcanoes, respectively.…”
Section: Northeast Japansupporting
confidence: 82%
“…In addition, it is found that increasing the dip angle (θ) of a slab in a subduction zone highly rotates the polarization direction of the fast S-wave (Figures 13 and 14), resulting in the polarization direction of the fast S-wave subnormal to the lineation (flow direction) with increasing dip angle, which can explain trenchparallel seismic anisotropy in a high-angle subduction zone. Because chlorite has a wide stability field at high pressure and high temperature in a mantle wedge and in a subducting slab (Hacker et al 2003;Fumagalli and Poli 2004;Padrón-Navarta et al 2010;Van Keken et al 2011;Till et al 2012;Wada et al 2012), the strong LPO of chlorite can be a source of the observed trench-normal or trench-parallel seismic anisotropy in the mantle wedge (Smith et al 2001;Currie et al 2004;Park et al 2004;Pozgay et al 2007;Long and Silver 2008;Huang et al 2011b;Wagner et al 2013) as well as in subducting slabs (Wagner et al 2013;Wang and Zhao 2013) depending on the dipping angle of slab in a subduction zone where chlorite is stable. International Geology Review 665…”
Section: Resultsmentioning
confidence: 99%
“…The polarization direction of the fast S-wave is often trench-normal in the back-arc area, but changes to trench-parallel in the fore-arc area (Smith et al 2001;Huang et al 2011aHuang et al , 2011b. This anisotropy can be attributed to the B-type olivine LPO (Jung and Karato 2001a;Kneller et al 2007).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Hiramatsu et al (1997) found that the subducting slab shows a strong anisotropy resulting from phase changes in the slab from shear-wave splitting analyses of ScS waves that travel from the events in the slab down to the deep mantle and are bounced back from the core-mantle boundary. Huang et al (2011b) further studied the anisotropic structure under NE Japan by analyzing shear-wave splitting of earthquakes that occurred in the upper crust, lower crust and in the double seismic zone within the subducting Pacific slab (Fig. 48).…”
Section: Seismic Anisotropy Tomographymentioning
confidence: 99%